EXPLORE THE IMPACT OF NOISE STRESS INDUCED BRAIN WAVE PATTERN AND BEHAVIOUR ALTERATIONS IN WISTAR ALBINO RATS - P, JEYAKUMARI; RAJAN, RAVINDRAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study is to investigate the impact of noise-induced stress and electroencephalogram (EEG) with behavioral alteration in male Wistar albino Rats. Methods: Adult albino rats were randomly divided into three groups. Each group contains six animals. Rats exposed to acute and sub-acute noise, stress (100 dB/4 h) were compared with control animals and assessed for learning and memory using an Eight-arm radial maze, Y-maze, T-maze and also monitoring of brain electrical activity showed by the electro encephalography. Results: The reference memory and working memory error increases, in acute and sub-acute noise stress. The amplitude and frequency also increase in frontal and occipital lobar when compared to control animals. Conclusion: Animals were exposed to noise stress showed learning and memory impairment and also changes in EEG wave pattern.